Patient journey experiences may contribute to improve healthcare for patients with rare endocrine diseases. Issue 12 (14th November 2022) - Webb, Susan M; Kristensen, Jette; Nordenström, Anna; Vitali, Diana; Amodru, Vincent; Wiehe, Lenja Katharina; Bolz-Johnson, Matt
Abstract : Patient journeys are instruments developed by EURORDIS, The Voice of Rare Disease Patients in Europe, to collect patients' experiences; they may identify gaps and areas deserving improvement, as well as elements positively considered by affected persons. As with other patient-reported experiences, they can complete the clinical evaluation and management of a specific disease, improving the often long diagnostic delay, therapy, patient education and access to knowledgeable multidisciplinary teams. This review discusses the utility of such patient-reported experience measures and summarises the experiences of patients with acromegaly, Addison's disease and congenital adrenal hyperplasia from different European countries. Despite rare endocrine diseases being varied and presenting differently, feelings of not having been taken seriously by health professionals, family and friends was a common patient complaint. Empathy and a positive patient-centred environment tend to improve clinical practice by creating a trustworthy and understanding atmosphere, where individual patient needs are considered. Offering access to adequate patient information on their disease, treatments and outcome helps to adapt to living with a chronic disease and what to expect in the future, contemplating the impact of a disease on patients' everyday life, not only clinical outcome but also social, financial, educational, family and leisure issues is desirable; this facilitates more realistic expectancies for patients and can even lead to a reduction in health costs. Patient empowerment with patient-centred approaches to these complex or chronic diseases should be contemplated more and more, not only for the benefit of those affected but also for the entire health system.